2018
DOI: 10.1111/tid.12817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low‐level BK polyomavirus viremia on intermediate‐term renal allograft function

Abstract: High-level viremia was associated with impaired graft function. In contrast, low-level BKPyV viremia had no significant impact on intermediate-term graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
3
19
0
1
Order By: Relevance
“…There is no clear definition that decreasing IS and clearing the virus will prevent the allograft kidney from an injury and a dimin- Interestingly, the delta eGFR they found was exactly the same we found in this study. 24 Our findings indicate that controlling viremia to low levels will not result in irreversible allograft damage. However, to decrease the immunosuppression cause a fear of developing rejection, although others have shown that an 80% or more decrease in viremia resulted in a fast viremia clearance 33 without increasing the incidence of acute rejection.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…There is no clear definition that decreasing IS and clearing the virus will prevent the allograft kidney from an injury and a dimin- Interestingly, the delta eGFR they found was exactly the same we found in this study. 24 Our findings indicate that controlling viremia to low levels will not result in irreversible allograft damage. However, to decrease the immunosuppression cause a fear of developing rejection, although others have shown that an 80% or more decrease in viremia resulted in a fast viremia clearance 33 without increasing the incidence of acute rejection.…”
Section: Discussionmentioning
confidence: 66%
“…Our patients presented a high incidence of viremia (51%) compared to others who report 19% to 42% . The viremia incidence may vary if one routinely collects viremia, as we did, from the second to the 12th month, or only collect viremia if urinary decoy cells are positive …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Drachenberg et al, a BKV level of more than 10 000 copies/mL was significantly associated with BKN. Similarly, a study by Korth et al found that low level BKV had no impact on graft function, failure, or rejection compared to patients with undetectable BKV, while high‐level BKV > 10 000 was associated with worse graft function, rejection, and higher rates of BKN. Additionally, in a small series of patients without BKN, BK viremia was not associated with a difference in graft function compared to recipients without BK viremia .…”
Section: Introductionmentioning
confidence: 92%